Studi Komparasi Penggunaan Model Pembelajaran Problem Based Learning Dan Project Based Learning Terhadap Keaktifan Siswa Kelas X Dalam Pembelajaran Ekonomi SMA Negeri 1 Bangsri Tahun Ajaran 2015/2016 - Indrawan, Yanuar Ishaq; , Drs. Djoko Suwandi, S.E, M.Pd (2016)
The purpose of this study was to determine: 1) to determine the increase students' active learning model Problem Based Learning on economic subjects in class X peminatan IPS 1 in SMA Negeri 1 Bangsri. 2) the improvement of students' active learning model Project Based Learning on economic subjects in class X peminatan IPS 2 in SMA Negeri 1 Bangsri. 3) to determine significant differences between the model of Problem Based Learning and Project Based Learning on the student's activity on economic subjects in class X and class specialization IPS 1 X 2 peminatan IPS in SMA Negeri 1 Bangsri. This research was conducted in SMA Negeri 1 Bangsri. This research method is experimental research design with true experimental design form posttest-only control design. The population in this study were students of class X peminatan IPS number of 159 students. Samples were taken from two classes of class X peminatan IPS 1 (experimental class) and class X pemniatan IPS 2 (control group). data collection techniques using purposive sampling method. Data collection technique used observation method uses a check list to determine the activity of students in accordance with the indicator. Data were analyzed using t test. Instructional material used in this study is a cooperative matter. The results of data analysis and discussion, it can be concluded that: 1) there are differences in student activity on economic subjects anatara learning model Problem Based Learning Project Based Learning model of learning in class X SMA Negeri 1 Bangsri the academic year 2015/2016 (as evidenced by the analysis research data by t test obtained t> t table, namely 8.895> 2.160 or significance level of <0.05 is 0.000, it can be concluded H0. 2) learning model Problem Based learning provides the level of student activity on economic subjects better than the using model Project Based learning in class X SMA Negeri 1 Bangsri the academic year 2015/2016. This is evidenced by the class using learning model Problem Based Learning has a percentage of the activity of an average 57% higher than the class that uses the Project Based Learning learning model having an average of 48%. Keywords: Problem Based Learning, Project Based Learning, Student Activity